ASN Kidney Health Guidance on the Cardiovascular-Kidney-Metabolic Syndrome - Nisha Bansal; Petter Bjornstad; Adam P. Bress; Tara I. Chang; Xingxing Cheng; Michelle M. Estrella; Alan S. Go; Amy K. Mottl; Sankar D. Navaneethan; Brendon L. Neuen; Brian S. Rifkin; Kim Zuber; et al. (Journal of the American Society of Nephrology, 2026)
Key Points The cardiovascular-kidney-metabolic (CKM) syndrome framework has important implications in the care of people with kidney diseases. Cardiovascular screening is important in people with kidney diseases, but the approach may differ in this high-risk population. Multiple pharmacotherapies for CKM syndrome offer significant cardiovascular and kidney benefits. Cardiovascular-kidney-metabolic (CKM) syndrome highlights the interconnected nature of cardiovascular disease, CKD, and metabolic dysfunction and underscores the need for integrated approaches to prevention and treatment. Patients with kidney diseases are at markedly elevated risk for atherosclerotic cardiovascular events, heart failure, kidney failure, and premature mortality across the spectrum of kidney disease severity. Recent advances in therapeutics, including sodium-glucose cotransporter 2 (SGLT2) inhibitors, glucagon-like peptide-1 (GLP-1)–based therapies, and nonsteroidal mineralocorticoid receptor antagonists, alongside established renin-angiotensin system inhibitors and lipid-lowering therapies, have transformed the management of CKM by demonstrating both cardiovascular and kidney benefits. However, important gaps remain in applying the CKM framework to patients with kidney diseases, particularly among individuals with advanced CKD, kidney failure treated with dialysis, kidney transplant recipients, younger and older individuals, and those with nonmetabolic kidney diseases including glomerular disorders. This American Society of Nephrology Kidney Health Guidance provides practical guidance for nephrology clinicians on screening, risk stratification, and pharmacologic management across the CKM spectrum. The guidance emphasizes the importance of longitudinal assessment of estimated glomerular filtration rate and albuminuria as foundational markers of cardiovascular and kidney risk, including the role of cardiac biomarkers and imaging. Integration of cardiovascular and kidney risk prediction models, including the American Heart Association Predicting Risk of Cardiovascular Disease EVENTs (PREVENT) equations and the Kidney Failure Risk Equation (KFRE), may support early identification of high-risk patients and guide treatment intensification. The guidance also reviews evidence supporting sequential and combination approaches to CKM therapies, strategies for managing adverse effects, and special considerations for CKD subpopulations where data are more limited. Adoption of a CKM framework in nephrology practice promotes coordinated, multidisciplinary care and provides an opportunity to shift from organ-specific management toward a more holistic approach aimed at reducing cardiovascular events, slowing kidney disease progression, and improving patient-centered outcomes across the continuum of kidney disease.